1991
DOI: 10.1111/j.2042-7158.1991.tb03510.x
|View full text |Cite
|
Sign up to set email alerts
|

Transport of cephalexin to the cerebrospinal fluid directly from the nasal cavity

Abstract: The aim of the present study has been to confirm the existence of a transport pathway for a drug (cephalexin) to the cerebrospinal fluid (CSF) directly from the nasal cavity, by comparing the drug's concentrations in CSF after intranasal (i.n.), intravenous (i.v.) and intraduodenal (i.d.) administration. Higher levels of the drug were found in CSF following i.n. administration compared with the i.v. and i.d. routes, even though its plasma concentrations were similar. These findings suggest the existence of a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(51 citation statements)
references
References 16 publications
3
47
0
1
Order By: Relevance
“…This has been shown among others for dihydroergotamine (Wang et al 1998), cocaine (Chow et al 1999), lidocaine (Chou & Donovan 1998) and cefalexin (Sakane et al 1991). The extracellular pathway, that transports polar drugs through tight junctions (see Epithelial cell barrier above) between sustentacular cells and olfactory neurons into the CSF, relies on a direct anatomic connection between the submucosa and the subarachnoid extensions, the perineural space surrounding the olfactory nerves, as they penetrate the cribriform plate ( Figure 6) (Jackson et al 1979).…”
Section: Transport Pathwaysmentioning
confidence: 99%
“…This has been shown among others for dihydroergotamine (Wang et al 1998), cocaine (Chow et al 1999), lidocaine (Chou & Donovan 1998) and cefalexin (Sakane et al 1991). The extracellular pathway, that transports polar drugs through tight junctions (see Epithelial cell barrier above) between sustentacular cells and olfactory neurons into the CSF, relies on a direct anatomic connection between the submucosa and the subarachnoid extensions, the perineural space surrounding the olfactory nerves, as they penetrate the cribriform plate ( Figure 6) (Jackson et al 1979).…”
Section: Transport Pathwaysmentioning
confidence: 99%
“…CSF was obtained by cisternal puncture with a 23-gauge needle connected to polyethylene tubing. Collection was terminated as soon as any blood began to appear in the tubing (24).…”
Section: Brain Dissection and Csf Collectionmentioning
confidence: 99%
“…This finding provides further evidence for a direct connection between the nose and the brain. A variety of substances, including metals (5,8), dyes (30), viruses (21), peptides (22,23), proteins (1,2,28) and drugs (4,24), have been reported to reach the brain from the nasal cavity, without having to cross the BBB.…”
Section: Introductionmentioning
confidence: 99%
“…It is also well-established that there exists a direct anatomical connection between the nasal cavity and the CNS by paracellular and transcellular pathway as well as through trigeminal neurons which suggest the scope of the development of CNS therapeutics for intranasal administration. Drugs such as sulfonamides (Sakane et al, 1991a), cephalexin (Sakane et al, 1991b), progesterone (Anand Kumar et al, 1982) and zidovudine (Seki et al, 1994) are reported to be successfully delivered to brain by intranasal route. Drugs presently in market such as estradiol for hormone replacement therapy, nicotine for smoking cessation, cyanocobalamin to treat vitamin B 12 deficiency, zolmitriptan and sumatriptan for migraine and cluster headache, buserelin for the treatment of prostate cancer, are other examples of intranasally administered drugs for systemic effect.…”
Section: Introductionmentioning
confidence: 99%